SEASONAL INCIDENCE OF INSECT - PESTS ON BRINJAL AND A NOTE ON THE BIOLOGY OF LEUCINODES ORBONALIS GUEN. (LEPIDOPTERA : PYRAUSTIDAE) IN MANIPUR. - SURESH, M.; BIJAYA, P.; PRASAD, B.; SINGH, T. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Brinjal, Solanum melongena Linn. is infested by a number of insect pests, viz. Aphid, Aphis gossypii Glover, Jassid, Amrasca biguttula biguttula Ishida, Epilachnabeetle, Epilachna vigintioctopunctata Fabr.: Leaffolder, Antoba (Eublemma) olivacea Walker and shoot and fruit borer, Leucinodes orbonalis Guen in Manipur. The aphids and the Jassids were active throughout the crop season with their peaks in the middle of February and first week of August, respectively. The Epilachnabeetle appeared on this crop in the middle of May with its peak in the first week of August. Activity of the Leaffolderstarted in the first week of March with its peak in the last week of March. Infestation of shoot by the brinjal borer was observed to be 17.2% during April and was maximum in fruits (57.5%) in the last week of May. Among these insect pests, the last one i.e. Leucinodes orbonalis Guen, has been observed to be a serious pests in this area. Its life cycle varies from 28 to 44 days. The egg, larval and pupal periods lasted for 5 to 7 days, 15 to 27 days and 8 to 10 days respectively, under the laboratory conditions of 27.25 ±4.24°C and 68.5 ± 10.5% RH.